2009
DOI: 10.1111/j.1574-0862.2009.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural nonfarm employment and farming: household‐level linkages

Abstract: This article introduces the articles in "Agricultural Economics", vol. 40 no. 2 (March 2009). First, we introduce their objectives in a brief review of existing literature on developing country trends in rural income diversification, in particular rural nonfarm employment (RNFE) and its impact on farm technology choice in crops and livestock, and thus on agricultural modernization and diversification. Then we preview the key points of the articles, which use distinctive primary datasets from Albania, Bulgaria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…These data seem to corroborate the hypothesis that an initial control over land can facilitate access to RNF services and businesses. This concentration of capital within a class of rich farmers can raise concerns about the possible future development trajectories of the region (Fort 2007; Davis et al. 2009; Lanjouw and Murgai 2009).…”
Section: Resultsmentioning
confidence: 99%
“…These data seem to corroborate the hypothesis that an initial control over land can facilitate access to RNF services and businesses. This concentration of capital within a class of rich farmers can raise concerns about the possible future development trajectories of the region (Fort 2007; Davis et al. 2009; Lanjouw and Murgai 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Reardon et al (1988), it is reported that in villages visited, 'local non-farm income is derived almost entirely from artisanal manufacture of mats, baskets, and tools, and services (primarily sorghum beer-making)', despite the fact that for decades, Burkina Faso has harboured one of the largest small-scale gold mining workforces in sub-Saharan Africa. Subsequent studies (Reardon, 1997;Davis et al, 2009) fail to address this shortcoming. Similarly, Bryceson (1996Bryceson ( , 2002, whose work provides a timely review of the region's 'rural livelihoods in transition' phenomenon, has also overlooked the importance of the ASM sector.…”
Section: A Disconnected Literaturementioning
confidence: 99%
“…Indeed, Haggblade et al (2010) note that rural nonfarm income (RNFI) is a main cash source of rural households in SSA, and Reardon et al, 1994, Davis et al, 2009 hypothesize that RNFI is a key cash source and determinant for input purchases, especially in the face of idiosyncratic failure of credit markets. Yet the empirical literature rarely compares household own-cash sources with credit as potential liquidity sources for farmers to buy inputs.…”
Section: Introductionmentioning
confidence: 99%